Health‐Related Quality of Life and Its Contributors According to a Preference‐Based Generic Instrument in Cirrhosis. Issue 3 (24th September 2021) - Hui, Yangyang; Li, Nan; Yu, Zihan; Li, Chaoqun; Wang, Xiaoyu; Li, Yifan; Sun, Mingyu; Yang, Wanting; Guo, Gaoyue; Fan, Xiaofei; Lin, Lin; Cui, Binxin; et al.
Abstract : It is essential to determine contributors around impairment in health‐related quality of life (HRQoL) in patients with cirrhosis aiming at improving health care and therapeutic strategy. Studies simultaneously incorporating disease severity based on biochemical parameters and other physical/psychological effects (i.e., sleep disturbance and frailty) are heterogeneous and the subject of the present study. We analyzed and compared HRQoL, using the EuroQol Group 5 Dimension (EQ‐5D) questionnaire and the utility index retrieved, in patients with cirrhosis and across groups stratified by sleep disturbance or frailty phenotype. Sleep disturbance and frailty were determined by the Pittsburgh Sleep Quality Index (PSQI) and Frailty Index, respectively. Multiple linear regression was implemented to clarify contributors of poor HRQoL. In this cohort of 227 patients with mean age of 61.7 years and 47.2% male, more than half of the study population represented impairment in HRQoL in at least one domain, according to EQ‐5D. Furthermore, sleep disturbance and frailty have proved to be independently associated with poor HRQoL in two separate regression models, whereas conventional scoring systems such as Child‐Pugh classification and Model for End‐Stage Liver Disease are not closely relevant. Intriguingly, not all health domains within EQ‐5D correlated well with PSQI and Frailty Index, with the exception of usual activities. Pain and anxiety/depression were the most frequently affected HRQoL domains even in patients without sleep disturbance or frailty. Conclusion: Impaired HRQoL is prevalent in patients with decompensated cirrhosis. Sleep disturbance and frailty are independently associated with poor HRQoL. It is imperative to timely intervene with these symptoms and deliver tailored health care. Abstract : We found more than half the patients with decompensated cirrhosis represent impairment in HRQoL, at least in one dimension, according to a generic patient‐reported instrument, that is, EQ‐5D. Moreover, pain and anxiety/depression appeared to be the most frequently affected HRQoL domains even in patients without sleep disturbance or frailty.image